Determinants of Financial Stability of the Banking Sector: Empirical Study - Elbadri, Marei M. Abdelhafid (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
The primary purpose of this thesis is to identify the main determinants of bank stability to build a practical framework for safeguarding financial stability by focusing on the two separate samples. Firstly, to investigate the bank stability determinants of Islamic banks and their conventional peers using a sample of 254 banks across the nine leading countries (QISMUT+3) dual banking systems over the period 2011-2017. Findings present a positive association between good governance, financial freedom, and bank stability. On the other hand, corruption and economic freedom have a damaging effect. The legal systems of countries do not show any enhancement effect over bank stability is one of the basic damaging effects. According to findings religiosity concentration improves stability, banks’ religiosity does not provide any stability advantage. Among the macroeconomic and bank-specific indicators, GDP growth and cost efficiency are the major stability determinants. Secondly, it is aimed to find out the relationship between oil and gold prices and the financial stability of Islamic banks operating in the Gulf Cooperation Council countries for 2005-Q1 to 2018-Q1. For this purpose, first, it uses Johansen cointegration and VECM methodologies. employs the newlydeveloped Bayer–Hanck, Gregory–Hansen, Toda–Yamamato, and DOLS methodologies to test the robustness of the findings. Results reveal a cointegrating relationship and equilibrium-correcting mechanism between the two commodities prices and the bank stability. Both commodities prices have positive effects on bank stability in the short run. However, the oil price has a positive impact in the long run, while the gold price has a negative effect on the long run. The causality results confirm unidirectional causality from oil and gold prices to bank stability in the short run and oil price to bank stability in the long run.

ÖZ: Bu tezin temel amacı finansal istikrarı korumak adına temel politikaların geliştirilmesi için banka istikrarının ana belirleyici etkenlerini iki farklı örnekleme dayanarak belirlemektir. İlk olarak İslami bankaların ve anlaşmalı şubelerinin, banka istikrar belirleyicilerini incelemek için 2011-2017 yılları arasında ikili bankacılık sisteminde önde gelen dokuz farklı ülkeden (QISMUT+3), 254 banka örnek olarak alınmıştır. Bulgular, iyi idare, finansal özgürlük ve banka istikrarı arasında pozitif bir ilişki olduğunu göstermektedir. Diğer yandan, yolsuzluk ve ekonomik özgürlüğün zarar verici bir etkiye sahip oldukları görüldü. Ülkelerin hukuk sistemlerinin, banka istikrarına, herhangi bir iyileştirme etkisinin olmadığı temel zarar verici etkenlerden biri olduğunu göstermemektedir. Sonuçlar, dindarlığın istikrarı geliştirdiğini gösterse de bankaların dindarlığı istikrar avantajı sağlamamaktadır. GSYİH büyümesi ve maliyet etkinliği, makroekonomik ve banka göstergeleri arasında istikrarın ana belirleyicileridir. İkinci olarak, 2005-Q1 ila 2018-Q1 için Körfez İşbirliği Konseyi ülkelerinde faaliyet gösteren İslami bankaların petrol ve altın fiyatları ile finansal istikrarı arasındaki ilişkiyi araştırmayı amaçlamıştır. Bu amaçla önce Johansen eşbütünleşme ve VECM yöntemleri kullanılmıştır. Ardından, bu sonuçların doğruluğunu ölçmek için yeni geliştirilen Bayer–Hanck, Gregory–Hansen, Toda–Yamamato ve DOLS yöntemleri kullanılmıştır. Sonuçlar, iki emtia fiyatları ile banka istikrarı arasında bir eş-bütünleşme ilişkisi ve denge düzeltme mekanizması açığa çıktığını göstermektedir. Her iki emtia fiyatının da kısa vadede banka istikrarı üzerinde olumlu etkileri mevcuttur. Ancak petrol fiyatlarının uzun vadede olumlu etkisi varken bu vadede altının olumsuz etkileri vardır. Nedensellik sonuçlarına bakıldığında, kısa dönemde petrol ve altın fiyatlarından banka istikrarına, uzun dönemde ise petrol fiyatından banka istikrarına doğru tek yönlü bir nedensellik olduğunu görülmektedir.
Doctor of Philosophy in Finance. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2021. Supervisor: Prof. Dr. Eralp Bektasş.
Keywords: Thesis Tez; Banking and Finance Department; Banks and Banking; Bank Stability; Institutional Environment; Religiosity; Macroeconomics; Gold Price; Oil Price